Faktor-Faktor yang Berhubungan dengan Pelaksanaan Penerapan Standar Asuhan Persalinan Normal Oleh Bidan Puskesmas Rawat Inap di Kabupaten Bungo Provinsi Jambi - Evrina Solvia Soleh; Masrul Masrul; Desmiwarti Desmiwarti (Universitas Batanghari Jambi, 2018)
Implementation of Standard Normal Birth Assembly is an integrated effort in reducing MMR and IMR. This activity is very important to be carried out considering that Bungo Regency has the highest maternal and infant mortality rates in Jambi Province. Several factors related to Standard Application of Normal Birth care in Bungo Regency are: Education, Training, Motivation, Perceptions of Rewards, Experience and Facilities. The objective of this research is to know factors related to the implementation of Normal Birth Standard by Inpatient Health Center Midwife in Bungo Regency. This study is an analytic observational study with a cross-sectional design of 47 midwives who served in Bungo Regency inpatient Health Center from July to September 2017. Respondents were interviewed and observed in implementing normal labor standards. Data processing was done by computerization and analyzed statistically using univariate, bivariate, and multivariate analysis with product moment correlation. There is a relationship between training with the implementation of normal labor standards (p = 0.001), there is a relationship between experience with the implementation of normal labor standards (p = 0.010). There is no correlation between perceptions of rewards and the implementation of normal labor (p = 0.539), there is no educational relationship with the implementation of normal labor standards (p = 0.404) and motivation with the implementation of normal labor standards (p = 1,000). The conclusion of this study is that training is the dominant factor that relates to the implementation of normal labor standards by midwives at the health center in Bungo regency..